(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
There is no consensus regarding the global prevalence of amputations1 but it has been estimated that that there were 1.6 million amputees in the United States in 2005 with a prevalence of 1 in 200 persons and with an alarming prediction of doubling of this figure by the year 2050.2 Diabetics have the highest prevalence of lower limb amputations with a frequency of one amputation occurring every 30 seconds globally.3 Currently lower limb amputees are mobilized and rehabilitated using conventional socket type prostheses.4 These conventional socket type prostheses are associated with a complications rate in over 60%5 amputees including stump ulcers and excessive sweating,6 prosthesis fitting issues due to fluctuations in stump size,7 residual limb fracture,8 lack of confidence and problems in mobility.9 To overcome these complications of socket prosthesis, osseointegrated prostheses have been designed.10